Análise experimental do funcionamento de um cluster via computação distribuída - PENA NETO, Lázaro Nogueira (2015)
This work explains the operation of a Beowulf compute cluster pattern. It develops the principle of physical construction of the cluster, and from there its logical organization systems. Internally the detailed study is the usage of a quantitative algorithm for specific calculations so that the magnitude of the calculations and operations can be distributed among the nodes in the cluster. With this study, it systematizes the procedures up, which could/can be applied to future jobs involving high performance and use of computers, the difficulties it is reported and also it outlines the planning and construction of this shared model.